Experimental verification of the numerically determined parameters for the non-linear two-axis model of a synchronous motor with interior permanent magnets - Hederić, Željko (JET on-line, 2021)
Synchronous machines belong to the family of electrical machines characterised by a synchronous magnetic rotating field in the air gap of the machine, the speed of which depends on the frequency of the currents in the armature winding. The paper presents procedures and methods for the numerical determination and experimental verification of the parameters for a nonlinear two-axis model of a synchronous motor with permanent magnets in the rotor (IPMSM) and a concentrated stator winding. To calculate the distribution of electro-magnetic fields in the motor accurately, models with distributed parameters are used in motor design, for which the Finite Element Method (FEM) is usually employed. The improvement by using the model with concentrated parameters considerably simplifies the physical model, by describing it with a system of (non)linear differential equations, the so-called partial differential equations, which is presented in this paper.
Keywords: flux linkage; interior permanent magnets; non-linear; synchronous motor